RECRUITMENT AND CADRE DEVELOPMENT MANAGEMENT FOR (KITAB KUNING) TEACHERS BASED ON THE AMTSILATI METHOD: CENTRAL JAVA REGION 1 COORDINATOR OFFICE - Kholilur Rohman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The role of the Amtsilati Coordinator in managing the recruitment and development of Amtsilati teachers is crucial for the success of improving the quality of education using the Amtsilati method in Central Java Region 1. This study attempts to examine the strategies, mechanisms, and effectiveness of the management of the Amtsilati Regional Coordinator of Central Java 1 in two main aspects: teacher recruitment and cadre development. This study applies a descriptive qualitative approach with data collection methods through literature reviews, review of Amtsilati Coordinator guideline documents, and documentation of the Central Java 1 Regional Coordinator program activities. This study reveals that the Amtsilati teacher recruitment system in the Central Java 1 Regional Coordinator is implemented through three mechanisms: the submission of Assigned Teachers from the Central Amtsilati Center, the utilization of Alumni who are willing to serve, and internal Korwil cadre development. The impact of the cadre development program is seen in the increase in the competitive quality of the institution, which is marked by the growth in the number of students, the increase in students' ability to read yellow books quickly, increased achievement, a high level of alumni satisfaction, and a positive response from parents. Obstacles that are still encountered include the limited number of qualified teachers and the need for more intense communication to distribute teachers optimally. This study recommends the need to strengthen the intensive teacher development program as a strategy for developing Amtsilati in the Central Java 1 Regional Coordinator.